(untitled) (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2026)
The purpose of this study was to analyze the effect of differentiated learning in improving student learning outcomes on harmonic vibration material in class XI. The study was conducted at MAN 2 Model Medan with a quantitative approach through experimental methods. The research sample consisted of class XI.F1A as the experimental class and XI.F1B as the control class. The results showed that the average pretest score of the experimental class was 29.12 which then increased to 85.88 in the posttest, while the control class had an average pretest score of 30.50 and a posttest of 79.50. Based on the t-test, there was a significant difference between the differentiated learning method and the conventional method (t count = 3.137 > t table = 1.984). The N-Gain Score analysis showed high effectiveness in the experimental class with a score of 80% (effective category) compared to the control class with a score of 74% (quite effective category). Thus, it can be concluded that the differentiated learning method has a significant impact on improving student learning outcomes on harmonic vibration material at MAN 2 Model Medan.